Public food grain storage facilities in Bangladesh: An assessment of functionality, repair needs, and alternative usage - Kabir, Razin; Yunus, Mohammad; Hossain, Tofazzal; Rashid, Shahidur (International Food Policy Research Institute, 2019)
Based on an extensive survey, this study assesses the current conditions of all three types of government owned warehouses: the silos, Central Storage Depots (CSDs), and Local Supply Depots (LSDs). Using a large team of civil engineers as enumerators, a detailed set of information is generated about the functionality, repair needs, as well as alternative uses of all public warehousing facilities. The data generated from the survey fed into the production of a user-friendly GIS database that encompasses the mapping of all storage facilities, along with functionality indicators and summary statistics from the survey. The comprehensive repair estimates generated in the course of this study, along with its supplementary GIS tool, can serve as important inputs to strategic policy decisions related to the public food grain storage system in the country.